Requirements - the Key to a Successful Project: The Significance of Clear Requirements in Project Success (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Business success canbe accomplished many different ways.   Generally the easiest and most costeffective way to accomplish change and success in an organization is via thebottom up approach. The reason for this is when an organization involves itsworkers in any change or improvements, the employees gain a sense of pride or afeeling of ownership. But all that possible when there are requirements.are what a project is all about.  This paper will take a look at howRequirements drive the project scope and unless well-defined and understood,can lead to huge increase in project scope.